Occupational upgrading and the business cycle in West Germany - Thomas Büttner; Peter Jacobebbinghaus; Johannes Ludsteck (Kiel Institute for the World Economy (IfW), 2009)
The occupational skill structure depends on the business cycle if employers respond to shortages of applicants during upturns by lowering their hiring standards. The notion and relevance of hiring standards adjustment was advanced by Reder and investigated formally in a search-theoretic framework by Mortensen. Devereux implements empirical tests for these theories and finds affirmative evidence for the U.S. labour market. We replicate his analysis using German employment register data. Regarding the occupational skill composition we obtain somewhat lower but qualitatively similar responses to the business cycle despite of well known institutional differences between the U.S. and German labour market. The responsiveness of occupational composition wages to the business cycle is considerably lower in Germany.
Keywords: J62; J31; J41; C24; 330; Hiring standards; business cycle adjustment; occupational upgrading; wage structure; wage setting; overqualification; Erwerbsverlauf; Arbeitsmobilität; Humanvermögen; Konjunktur; Qualifikation; Lohnstruktur; Überqualifikation; Deutschland